Information acquisition and liquidity dry-ups - Philipp Koenig; David Pothier (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
We analyze a novel feedback mechanism between market and funding liquidity that causes self-fulfilling liquidity dry-ups. Financial firms facing funding withdrawals have an incentive to acquire information about their assets. Those with good assets gain by resorting to outside liquidity sources and withhold assets from secondary markets. This leads to adverse selectrion and lowers market prices. If prices fall by enough, funding withdrawals are amplified and market and funding illiquidity become mutually reinforcing. We compare different policy measures that can mitigate the risk of inefficient liquidity dry-ups. While outright debt purchases can implement the efficient allocation, liquidity injections may backfire and exacerbate adverse selection.
Keywords: D82; G01; G12; 330; Information Acquisition; Market Liquidity; Financial Crises